Age, duration of work, noise and vibration in inducing hearing and balance impairments (Faculty of Medicine Universitas Indonesia, 2005)
Noisy and vibrating bajaj, a public transportation in Jakarta, is a potential risk in inducing hearing and balance problems. Bajaj drivers in the Jakarta area were chosen by consecutive sampling and examined medically in the Neurotological Subdivision of the ENT Department of the Cipto Mangunkusumo Hospital, Jakarta. Hearing and balance impairments were then diagnosed from audiometric and posturographic tests. The study was carried out from March 2000 until October 2001. A number of 350 bajaj drivers participated in this study. There were 97 subjects without hearing and balance impairments, and 96 subjects suffered from hearing and balance impairments. Compared to drivers aged less than 40 years, those aged 41 years or more had a four-fold increased risk of developing hearing and balance impairments [adjusted odds ratio (OR)=3.90; 95% confidence interval (CI)=1.67-9.01. Drivers working 9 hours or more a day had an increased risk 2.3 times of developing hearing and balance impairments compared those working less than 9 hours a day (adjusted OR=2.32; 95% CI=I.22-4.41). Furthermore, when compared to those who had been working for 1-5 years, those who had been working for 5 years had an increased tendency of developing hearing and balance impairments. Those who had been working 21-30 years had a seven-fold increased risk of developing hearing and balance impairments (adjusted OR=7.11; 95% CI=1.88-26.92). To minimize hearing and balance impairments bajaj drivers are recommended to work less than 8 hours a day. (Med J Indones 2005; 14: 101-6) Keywords: noise, vibration, hearing, balance impairments, driver